2020
DOI: 10.1111/vsu.13387
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral lucencies of the proximal tibia in 17 horses

Abstract: Objective: To describe subchondral lucencies (SCL) in the equine proximal tibia, several treatment options, and clinical outcomes.Study design: Retrospective study.Animals: Seventeen horses with proximal tibial SCL. Methods: Medical record and radiograph review. Follow-up was obtained via examination and radiography when possible and by telephone and race records when required. The median duration of follow-up was 20 months (range, 0-48).Results: Proximal tibial SCL were associated with lameness in 14 of 17 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…The mechanical behavior of a specimen is determined by both geometry and material properties, 19 and clinical conclusions generated by this simplified MFC model should be made cautiously. However, the successful treatment of equine SCL in multiple locations after screw placement indicates a positive effect on bone healing 2,20,21 . Finite element modeling has predicted some aspects of bone mechanics 11,12 that are confirmed by this model and is a first step in understanding the practical mechanics of bone void failure and the impact of screw placement.…”
Section: Discussionmentioning
confidence: 62%
“…The mechanical behavior of a specimen is determined by both geometry and material properties, 19 and clinical conclusions generated by this simplified MFC model should be made cautiously. However, the successful treatment of equine SCL in multiple locations after screw placement indicates a positive effect on bone healing 2,20,21 . Finite element modeling has predicted some aspects of bone mechanics 11,12 that are confirmed by this model and is a first step in understanding the practical mechanics of bone void failure and the impact of screw placement.…”
Section: Discussionmentioning
confidence: 62%
“…Ruhe und kontrollierte Bewegung , ggf. ergänzt durch Behandlung mit nicht-steroidalen Antiphlogistika , sind unspezifische Maßnahmen, die insbesondere bei jungen, lahmfreien Pferden mit kleinen SCL 34 , 35 als initiale Therapie eingesetzt werden. Die Erfolgsaussichten sind hierbei allerdings variabel 3 , 36 und Rezidive häufig 8 .…”
Section: Therapieunclassified
“…Fully threaded screws used in lag fashion create compression when the tip end of the screw gains purchase in the far bone material and the screw head acts as a buttress 8,9 . The positive clinical results obtained after lag screw insertion in an MFC SCL 5 supports the clinical use of a lag screw to generate compressive force, but quantitative assessment of lag screw placement is surprisingly sparse in the literature 10 . For lag screws across MFC SCL, adequate MFC axial bone is necessary to achieve purchase of tip threads.…”
Section: Introductionmentioning
confidence: 99%
“…2 A study in 2015 reported that placement of a transcondylar lag screw as a treatment for equine medial femoral condyle (MFC) SCL resulted in similar or superior rates of lameness resolution and bone healing, 3 and other studies reported similar results in other locations. 4,5 The proposed mechanism is that the SCL directs strain around the void and screws create a compressive force across the SCL, redirecting strain and resulting in bone formation stimulus. 6 The technique was developed empirically, as direct measurement of bone strain in the MFC is impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation